2007
DOI: 10.1097/01.sla.0000255595.98041.6b
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Endotoxin Participates in Causing a Panenteric Inflammatory Ileus After Colonic Surgery

Abstract: Selective colonic manipulation initiates a distant inflammatory response in the small intestinal muscularis that contributes to postoperative ileus. The data provide evidence that gut-derived bacterial products are mechanistically involved in the initiation of this remote inflammatory cascade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 36 publications
4
41
1
Order By: Relevance
“…The motility alterations at distance of an inflammatory region we reported here bear resemblance to the panenteric field effect as described for postoperative and septic ileus and may possibly involve similar pathophysiological mechanisms (10,15,52).…”
Section: Discussionmentioning
confidence: 65%
“…The motility alterations at distance of an inflammatory region we reported here bear resemblance to the panenteric field effect as described for postoperative and septic ileus and may possibly involve similar pathophysiological mechanisms (10,15,52).…”
Section: Discussionmentioning
confidence: 65%
“…Another hint to the involvement of luminal pathogens was also shown by Türler et al in a model of colonic manipulation [60]. One should note that this model differs from the more commonly used small bowel manipulation as the large bowel contains log numbers more bacteria and bacterial degradation product that can act as innate immune stimuli.…”
Section: Barrier Dysfunctionmentioning
confidence: 88%
“…Surgical manipulation of the colon initiates a complex inflammatory cascade within the colonic muscularis, which is characterized by the release of inflammatory mediators and the recruitment of leukocytes (Tü rler et al, 2002). Recently, it was shown that selective colonic manipulation also initiates a distant inflammatory response in the small intestinal muscularis that significantly contributes to the pan-enteric development of POI (Tü rler et al, 2007). Therefore, we sought to determine whether the postoperative inflammatory response within both the colonic and small intestinal muscularis, which has been shown to settle within 6 to 24 h after surgical manipulation, would be altered by rosiglitazone treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Despite this novel insight, there is no pharmacological treatment yet available to prevent this postoperative event. In the present study, we Previous studies have demonstrated that surgical manipulation of the colon initiates an inflammatory cascade within both the colonic and small intestinal muscle layer that consists of 1) the induction of proinflammatory cytokines, chemokines, and adhesion molecules; 2) the additional recruitment of circulating leukocytes into the muscularis; and 3) the release of kinetically active substances, such as NO and prostaglandins, that directly inhibit smooth muscle contractility (Tü rler et al, 2002(Tü rler et al, , 2007Bauer and Boeckxstaens, 2004). Herein, we show that pretreatment of mice with rosiglitazone significantly attenuates these intestinal muscularis inflammatory responses, an effect that was abrogated by the PPAR␥ antagonist GW9662.…”
Section: Discussionmentioning
confidence: 99%